Strategi Komunikasi Politik Bakomstra Partai Demokrat dalam Rehabilitasi Elektabilitas Pasca Konflik Moeldoko - Sarifudin, Impron; Sari, Yunita; Hadiati, Hadiati (Jurnal Dinamika Ilmu Komunikasi, 2025)
In Indonesia’s political history, leadership struggles within political parties are not uncommon. Major parties such as PDIP, PKB, Golkar, PPP, and Hanura have experienced similar internal conflicts. However, the 2022 leadership dispute within the Democratic Party is distinctive because the main actor, Moeldoko, was not a party member but an active government official. This incident represents a new form of political leadership crisis that threatens the integrity of Indonesia’s democratic process. This study aims to analyze the political communication strategies of the Democratic Party’s Strategic Communication Agency (Bakomstra) in rebuilding the party’s electability after the conflict with Moeldoko. Employing a qualitative method, the study applies Suwandi’s (2000) model of political communication strategy, which includes objectives, audience, strategy, tactics, budget, timing, and evaluation. The findings reveal that Bakomstra implemented an open communication strategy through press conferences, media publications, and massive digital campaigns. Social media content was strategically produced to strengthen public support for Agus Harimurti Yudhoyono (AHY) while portraying Moeldoko as a political adversary. This approach effectively restored public trust and improved the Democratic Party’s electability.